Firm level multinationality in international business and finance - Berrill, Jenny (Trinity College (Dublin, Ireland). Trinity Business School, 2009)
The Multinational Corporation (MNC) is one of the most important concepts in international business (IB) and international finance (IF). However, there is no commonly and widely agreed definition of what constitutes an MNC and no classification system for the many types of MNCs that exist. This lack of definitional consistency has curtailed theoretical advances and caused confusion in comparing the results of empirical studies. This thesis proposes a matrix of multinationality that can aid scholars to overcome the problems resulting from a lack of comparability in studies of the MNC. This matrix forms part of a broader taxonomic classification of firms. This taxonomic classification system uses six high-level descriptors; type (public, private listed, private unlisted), industry (SIC codes), age (years, based on the date of incorporation), size (sales), location (country of headquarters), and degree of internationalisation (a matrix of multinationality based on the breadth and depth of operations across countries and regions).
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin